QRS Detection Optimization in Stress Test Recordings Using Evolutionary Algorithms - Hernando, David; Bailón, Raquel; Almeida, Rute; Hernández, Alfredo (Jornada de Jóvenes Investigadores del I3A, 2017)
QRS detection in exercise stress test recordings remains a challenging task because they are highly non-stationary and contaminated with noise. An algorithm to find the optimal set of parameters for QRS detection in these recordings is proposed. The performance improves up to 10.46 % in noisy recordings.